Realizm naukowy a hipoteza ciemnej materii i ciemnej energii - Pabjan, Tadeusz (Filozofia Nauki, 2022)
One of the essential aspects of the dispute between scientific realism and anti-realism is the question of the ontological status of unobservable objects assumed by scientific theories and models. Scientific realism claims that these objects exist in the natural world, while anti-realism denies this. The missing mass problem is a good example of an issue that requires that this question be resolved. In cosmology, this problem is solved by assuming the presence of dark matter and dark energy. The difficulty, however, is that experience does not provide direct evidence for the existence of these two „substances.” In the first part of the article, the differences between scientific realism and anti-realism are discussed. In the second and third parts, the problem of the missing mass is presented (special attention is paid to the difficulties with the empirical confirmation of the existence of dark matter and dark energy). The fourth part of the article discusses the arguments of the supporters of half-realism, which is a kind of compromise between scientific realism and anti-realism.